LivestockPlus: The sustainable intensification of forage-based agricultural systems to improve livelihoods and ecosystem services in the tropics - Rao, Idupulapati M.; Peters, Michael; Castro, A.; Schultze-Kraft, Rainer; White, D.; Fisher, M.; Miles, John W.; Lascano Aguilar, Carlos Eduardo; Blümmel, Michael; Bungenstab, D.J.; Tapasco, Jeimar; Hyman, Glenn G.; et al. (International Center for Tropical Agriculture, 2015)
As global demand for livestock products (such as meat, milk, and eggs) is expected to double by 2050, necessary increases to future production must be reconciled with negative environmental impacts that livestock cause. This paper describes the LivestockPlus concept and demonstrates how the sowing of improved forages can lead to the sustainable intensification of mixed crop–forage–livestock–tree systems in the tropics by producing multiple social, economic, and environmental benefits. Sustainable intensification not only improves the productivity of tropical forage-based systems but also reduces the ecological footprint of livestock production and generates a diversity of ecosystem services (ES), such as improved soil quality and reduced erosion, sedimentation, and greenhouse gas (GHG) emissions. Integrating improved grass and legume forages into mixed production systems (crop–livestock, tree–livestock, crop–tree–livestock) can restore degraded lands and enhance system resilience to drought and waterlogging associated with climate change. When properly managed tropical forages accumulate large amounts of carbon in soil, fix atmospheric nitrogen (legumes), inhibit nitrification in soil and reduce nitrous oxide emissions (grasses), and reduce GHG emissions per unit livestock product. The LivestockPlus concept is defined as the sustainable intensification of forage-based systems, which is based on three interrelated intensification processes: genetic intensification – the development and use of superior grass and legume cultivars for increased livestock productivity; ecological intensification – the development and application of improved farm and natural resource management practices; and socio-economic intensification – the improvement of local and national institutions and policies, which enable refinements of technologies and support their enduring use. Increases in livestock productivity will require coordinated efforts to develop supportive government, non-government organization, and private sector policies that foster investments and fair market compensation for both the products and ES provided. Effective research-for-development efforts that promote agricultural and environmental benefits of forage-based systems can contribute towards implemention of LivestockPlus across a variety of geographic, political, and socio-economic contexts.